Toleransi Hadist Multikultural : Analisis Uji Kualitas Sanad Dan Matan Hadist Shahih Muslim 1593 - Agus Sholahudin Shidiq; Farida Isroani (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
this article will present a discussion that focuses on the discussion of Hadith within the scope of multicultural, more precisely one of the existing multicultural values, namely about tolerance. There are several Hadiths that explain the importance of cultivating tolerance to deal with various differences. Because the Hadith is the second source of law after the Qur'an, it is necessary to analyze more deeply regarding the quality of the isnaad and its mat. Researchers use qualitative research methods, which refer to sources related to literature. The results of this study are, especially in Sahih Muslim hadith No. 1593, it can be concluded that the explanation related to the command to respect the body, even though the body comes from the Jewish religion, must still stand if the body passes, because this is one of the forms of tolerance that exists, and also respect for death itself. And there are many Isad in this Hadith that is Tsiqah, until it is concluded with Sahihul Isnad. And matan there are also syadz, even many of the Hadiths that explain a similar explanation, and there are also many verses of the Qur'an that support the exposure of the same discussion, and it can be concluded that the Hadith Sahih Muslim No. 1593 which discusses the chapter of the body, and related to this form of tolerance is Sahih.